2017
DOI: 10.1111/1365-2656.12703
|View full text |Cite
|
Sign up to set email alerts
|

Estimating demographic contributions to effective population size in an age‐structured wild population experiencing environmental and demographic stochasticity

Abstract: A population's effective size (N ) is a key parameter that shapes rates of inbreeding and loss of genetic diversity, thereby influencing evolutionary processes and population viability. However, estimating N , and identifying key demographic mechanisms that underlie the N to census population size (N) ratio, remains challenging, especially for small populations with overlapping generations and substantial environmental and demographic stochasticity and hence dynamic age-structure. A sophisticated demographic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 89 publications
(176 reference statements)
1
29
0
Order By: Relevance
“…2016; Trask et al. 2017). This is due to the fact that demographic variance and genetic drift arise from stochastic contributions that are independent among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…2016; Trask et al. 2017). This is due to the fact that demographic variance and genetic drift arise from stochastic contributions that are independent among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The Pleistocene seriously affected the structure of most birds (Hewitt CD, 2000;Greer, 2013). Nevertheless, quite a few studies have discovered that the populations during the interglacial period were stable (Marín et al, 2013;Zhu et al, 2018), while other studies have shown that gene flow and genetic diversity are vital for population existence and evolution (Clement and Crandall, 2000;Trask et al, 2017). the pattern of sex-biased dispersal of the silver pheasant and its influencing factors and to determine whether and how the interglacial period affected the population structure, gene flow, genetic diversity, and dynamics of the silver pheasant in southern China.…”
Section: Introductionmentioning
confidence: 99%
“…Only one demographic method allows demographic stochasticity and heterogeneity at the expense of challenging data demands such as individual-level information (Engen, Lande, Saether, & Gienapp, 2010). This might explain why the method has not been much used so far (but see Trask, Bignal, McCracken, Piertney, & Reid, 2017).…”
mentioning
confidence: 99%